Intensification of the Process of Extracting Non-Ferrous Metals from Kazakhstani Technogenic Raw Materials - Zhanserik Shoshay (AIDIC Servizi S.r.l., 2021)
The article proposes an environmentally friendly method for processing industrial waste by the example of slags from the Balkhash copper smelting plant (Kazakhstan). The first stage involved copper extraction. The second stage is gold recovery. For a more complete extraction of copper, microwave activation was used at various stages of the process. As a result, the recovery of copper using microwave radiation was 91 %, zinc 87.2 % and iron 94 % and without copper 65.7 %, zinc 84.6 % and iron 93.4 %, respectively. Such efficiency of copper recovery allows using thiourea as a reagent for gold recovery and avoiding the use of cyanides.